Legal Protection For Investors In Online Investment Agreements - Mayrine, Clara; Agustina, Dewi; Zulkifli, Suhaila; Noor, Tajuddin (LPPM Universitas PGRI Sumatera Barat, 2024)
Investment plays an important role in the economic sector, especially in developing countries such as Indonesia which is very strategic. Without sufficient investment, it is difficult to expect high economic growth that results in economic welfare for developing countries. This study also uses a normative legal approach, namely conducting field research on events that give rise to the principle of subrogation and the implementation of the principle of subrogation in online investment agreements which examines legal protection for fraudulent investment investors. The results of the study show that in practice Sunton Capital does not meet the provisions of the Commodity Futures Trading Law because it does not have certification from Bappebti, which indicates that its investment activities are illegal. Sunton Capital also offers high returns that are not proven, so it has the potential to be a form of fraud against investors. To prevent the increasing prevalence of illegal investment, preventive and repressive legal protection efforts are needed. Preventive efforts are carried out through education and socialization by Bappebti and OJK to increase public awareness of legal and safe investments. Meanwhile, repressive efforts involve law enforcement against perpetrators of illegal investments, including investigation, prosecution, and imposition of sanctions in accordance with Article 378 of the Criminal Code concerning criminal acts of fraud. In addition, victims of illegal investments have the right to obtain restitution in the form of compensation for lost assets, medical costs, and counseling services as regulated in the Witness and Victim Protection Law. However, because illegal investments such as Sunton Capital do not have a clear legal basis, direct compensation from the broker is often difficult to obtain